Will AI Take My Job? Evolving Perceptions of Automation and Labor Risk inLatin America - Cremaschi, Andrea; Lee, Dae Jin; Leonelli, Manuele (My University, 2025)
As artificial intelligence and robotics increasingly reshapethe global labor market, understanding public perceptions ofthese technologies becomes critical. We examine how theseperceptions have evolved across Latin America, using surveydata from the 2017, 2018, 2020, and 2023 waves of the Lati-nobar ́ometro. Drawing on responses from over 48,000 indi-viduals across 16 countries, we analyze fear of job loss due toartificial intelligence and robotics. Using statistical modelingand latent class analysis, we identify key structural and ideo-logical predictors of concern, with education level and polit-ical orientation emerging as the most consistent drivers. Ourfindings reveal substantial temporal and cross-country vari-ation, with a notable peak in fear during 2018 and distinctattitudinal profiles emerging from latent segmentation. Theseresults offer new insights into the social and structural dimen-sions of AI anxiety in emerging economies and contribute to abroader understanding of public attitudes toward automationbeyond the Global North
Keywords: 53 Ciencias Económicas::5306 Economía del cambio tecnológico ::5306.02 Innovación tecnológica; ODS 8 - Trabajo decente y crecimiento económico